The Father Figure in Anne Tyler's The Accidental Tourist - Alias, Merna Thaer; Hashim Taher, Isra (Al-Adab Journal, 2021)
The father figure has been a dominant theme in the works of the American southern novelist Anne Tyler (1941- ). She explores the psyche of male characters and tries to shed light on the struggles that the postmodern men go through in their daily life. She utilizes the chaos that occurs in their life to highlight their development. Family plays a major role that helps the father to understand the world around him. The Accidental Tourist (1985) tells the story of Macon Leary, a father who loses his only son and falls into grief. He loses his aim in life until he meets a woman called Muriel, who changes many things about him.